Encountering Place: Mapping and Location-Based Games in Interdisciplinary Education. (3rd July 2018) - Pánek, Jiří; Gekker, Alex; Hind, Sam; Wendler, Jana; Perkins, Chris; Lammes, Sybille
ABSTRACT: In this paper we propose the use of 'Encountering' a location-based game (LBG) based on the Wherigo platform to facilitate interdisciplinary student learning about places on field courses. Deploying a mobile, digital map-based platform addresses significant challenges – such as the sacrifice of context specificity and methodological applicability and depth. It also runs the danger of 'gamifying' the fieldwork, blinding the participant to their own agency and emergent encounters. Interactive and layered digital map interfaces have affordances that can potentially overcome such challenges. We claim that one such affordance is the ability to play through the map. In other words, maps – and digital maps in particular – offer the possibility of decoupling results-orientated actions from free-form serendipitous engagement with the field. Our argument is two-fold. First, that LBG toolsets such as Wherigo can provide a 'common ground' for students engaging in place-based interdisciplinary research, by providing a material, cartographic basis for playful investigation. Second, that they can facilitate the production of 'spaces of epistemological failure', allowing students to challenge taken-for-granted conceptual and methodological axioms within and across disciplines.